(untitled) (Journal of the College of Basic Education, 2022)
Praise be to God, Lord of the worlds, and prayers and peace be upon the Seal of the Prophets and Messengers, and whoever called with his call and was guided by a gift until the Day of Judgment, our Prophet Muhammad, may God’s prayers and peace be upon him, the best prayer and the most complete delivery.And after:The subject of scientific miracles is one of the modern topics, and many researchers may not study it in depth, and because it is a broad science with its controls and ramifications, I wanted to address it, albeit in a simplified way, because it is one of the important basics that enlighten man with the existence of the Creator, the Blessed and Exalted, that Western scientists, despite not embracing them For Islam, except that they were dazzled by the miracles in this universe, so how can we Muslims not go into the midst of this divine miracle?